Generation of chirp-controllable circularly polarized terahertz radiation in magnetized plasma. (18th June 2021) - Jiao, Zhi-Hong; Wei, Bo-Ning; Wang, Guo-Li; Zhao, Song-Feng
Abstract: We propose a promising way to generate chirp-controllable circularly polarized terahertz waves from a magnetized Ar plasma driven by a linearly polarized laser. With an inhomogeneous static magnetic field, the local electrons are subjected to different strengths of the Lorentz force and emit terahertz waves with different cyclotron frequencies. In addition, the chirp rate and the temporal waveform of this chirped terahertz field can be adjusted by varying the gradient of the static magnetic field and the gas-density distribution.